Phylogeographic and molecular characterization of Pronghorn spiny lobster (Panulirus penicillatus Olivier, 1791) in the Southern Coast of Java and Lombok, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Irwani, Wijayanti DP, Satria AW, Sabdono A. 2020. Phylogeographic and molecular characterization of Pronghorn spiny lobster (Panulirus penicillatus Olivier, 1791) in the Southern Coast of Java and Lombok, Indonesia. Biodiversitas 21: 5691-5697. Panulirus penicillatus is one of the most important lobster species in Central Java. It is one of the most populous species in the southern part of Java and Lombok. However, uncontrolled catching causes a decrease in the population of P. penicillatus. Despite such human threats, information about the taxonomic status of this species is limited. Several previous reports on the taxonomy of this species have always been based on the morphological features that cause ambiguous identification. Therefore, this study aimed to establish the relationships of P. penicillatus in southern parts of the southern part of Java and Lombok by using the molecular technique. Twelve samples were collected from four study areas of the southern coast of the southern part of Java and Lombok and identified using DNA barcoding technique. DNA barcoding technique was used for the first time to identify P. penicillatus in this region. This study demonstrated that all specimens belonged to P. penicillatus. However, one specimen (PPK-06) showed high intraspecies nucleotide divergence that formed a distinct subclade. Therefore, the specimen (PPK-06) could represent a cryptic species within P. penicillatus that needs to be studied further.
Keywords: Cluster analysis, DNA barcoding, Java, Lombok, Panulirus penicilatus, south coast